Using the Weather Index Classification System for Canadian Forest Fires over the Al-Jabal Al-Akhdar in Libya - Ben Miloud, Haifa M. (Scientific Journal of University of Benghazi, 2024)
Due to the noticeable change in temperatures in the world as a whole, fires in forests have become more prevalent in the summer. The current study sheds light on using the Canadian classification of forest burning on Al-Jabal Al-Akhdar in Libya, it aims to study the climatic variation of the fire weather index in Libya for the 24-27th day of July at noon for a long period 1940-2022. For Fire Weather Index (FWI) to occur, it is necessary to go through levels and analyze their data. The first level, which is the Fine Fuel Moisture Code (FFMC) code, is high in the middle and extends to the south of the region, while the Duff Moisture Code (DMC) code decreases in the north of the region and increases in the south. However, the Drought Code (DC) code shows the increase and decrease in the south as we head north, while in the second level, the Initial Spread Index (ISI) shows that it is high in the middle of the region. The Build-Up Index (BUI ) increases to the south and decreases to the north, and for the occurrence of the Fire Weather Index (FWI) in the third level, it reaches above 60, and thus it is considered very high, and this was clear on the 24th and decreased on the 27th during the period 1940-2022 for July at 12 noon. When dividing the periods from 1940-1981 and 1982-2022, it becomes clear that the first period is more widespread than the second period, and the intensity of the second period is higher than the first period. This indicates climate change in temperatures and the occurrence of drought. Over the coming years, the fire weather index will increase in the future.